Contribuição ao estudo das relações dos conectores maiores de próteses parciais removíveis com tecidos gengivais - Bacigalupo, João Carlos Carvalho de [UNESP] (1994)
The effect in the gingival tissue of four distinctive types of relationships between the major conector and the gingival margin was investigated in eight subjects in association with the experimental gingivitis model. The subjects wore appliances constructed in acrylic resin (retained by means of embrasure hooks) throughout the day an night, except during meals. After the appliances had been placed, the subjects were abstained from any oral hygiene for twenty-one days. Records of the Plaque Index, Gingival Index and probing deplh were taken at baseline and at each week. Data showed that there was a small increase in the Plaque Index and Gingival Index for the four areas and that the degree of inflammation of the covered areas was higher in the area without relief